Pengembangan Media Pembelajaran Scrapbook untuk Meningkatkan Pemahaman Materi Struktur Bumi dan Dinamikanya (UPEJ Unnes Physics Education Journal, 2019)
Some of Physics Science material in Junior High School are abstract so that sometimes students find difficulties in understanding them because there is no clear visualization of the material. Those things can be overcome by using a learning media. Scrapbook is a craft that contains images and a little narration which can help teachers in explaining some of the Physics Science material that requires a good visualization. This study aimed to develop scrapbook learning media and find out the effect of the learning media on students' material understanding. The method that was used in this research was Research & Development (R & D). The sample of this study were 27 students of VIIC class of SMP Negeri 1 Sigaluh using pretest-posttest and feasibility questionnaires. The data analysis techniques used t-test to see the difference between students’ learning result before and after the use of scrapbook as a media in the learning activities. Moreover, an N-gain test was also performed to calculate the amount of increase that was occured. The results of this study showed that scrapbook learning media did not only emphasize on the clear and interesting images, but also provided enough materials so that the media can be used for independent learning. The results of the feasibility test by material experts and media experts obtained an average score of 91.26% with a very feasible category. Scrapbook media was able to give an influence to the enhancement of students’ material understanding by obtaining an N-gain value of 0.54 with a medium category.